Effects of Interval Walking on Physical Fitness in Middle-Aged Individuals - Sophie Lalande PhD; Kazunobu Okazaki PhD; Toshiaki Yamazaki; Hiroshi Nose MD, PhD; Michael J. Joyner MD; Bruce D. Johnson PhD (SAGE Publishing, 2010)
The purpose of this study is to examine the effects of a 3-month interval walking program on peak aerobic capacity and cardiovascular risk factors in middle-aged sedentary individuals. Participants were divided into 2 groups: a nontraining control group (n = 17) and an interval walking training group (n = 29). Participants in the interval walking training group were instructed to perform 5 or more sets of 3-min low-intensity walking interspersed by 3-min of moderate to high-intensity walking (>70% of peak aerobic capacity) on 4 or more days/week. Measurements of peak aerobic capacity, blood pressure, blood lipids, and glucose concentration were performed before and after training. Twenty-six individuals completed the interval walking program averaging 4 days/week for 34 min, of which 16 min were moderate to high-intensity walking, with a total energy expenditure of 776 kcal/week. Three months of interval walking increased peak aerobic capacity (from 20.4 ± 3.0 to 26.0 ± 5.2 mL/kg/min; P < .001) and reduced resting systolic blood pressure (127 ± 11 to 119 ± 11 mm Hg; P = .01). There was an inverse correlation between initial level and training-induced changes in glucose, HbA1c, high-density lipoprotein, and low-density lipoprotein. Conversely, 3 months of nontraining did not improve physical fitness or cardiovascular risk factors. Very modest amounts of aerobic exercise involving brief periods of interspersed higher intensity exercise can significantly increase peak aerobic capacity and reduce resting systolic blood pressure in middle-aged sedentary individuals and contribute to a normalization of cardiovascular risk factors in individuals with elevated initial values.